Wound-Induced Polyploidy Is Required for Tissue Repair - Losick, Vicki P. (Adv Wound Care (New Rochelle), 2016)
Significance: All organs suffer wounds to some extent during an animal's lifetime and to compensate for cell loss, tissues often rely on cell division. However, many organs are made up of differentiated cells with only a limited capacity to divide. It is not well understood how cells are replaced in the absence of cell division. Recent Advances: Recent studies in the model organism Drosophila melanogaster have proven that wound-induced polyploidy (WIP) is an essential mechanism to replace tissue mass and restore tissue integrity in the absence of cell division. In this repair mechanism, preexisting differentiated cells increase their DNA content and cell size by becoming polyploid. Critical Issues: Cells within mammalian organs such as the liver, heart, and cornea have also been observed to increase their DNA ploidy in response to injury, suggesting that WIP may be an evolutionarily conserved mechanism to compensate for cell loss. Future Directions: The Hippo signal transduction pathway is required for differentiated cells to initiate WIP in Drosophila. Continued studies in Drosophila will help to identify other signaling pathways required for WIP as well as the conserved mechanisms that polyploid cells may play during wound repair in all organisms.